(3a+1)²-3a
Скобку (3a+1)² можно раскрыть формулой (a+b)² = a² + 2ab + b²
(3a+1)² = 9a²+6a+1
9a²+6a+1-3a
9a²+3a+1, сопоставим a=4
9×4²+3×4+1 = 9×16+3×4+1 = 157
ответ: 157
193
Объяснение:
(3a+1)^2 - 3a = 9a^2 + 6a +1 - 3a = 9a^2 + 3a + 1
Якщо а = 4, то
9a^2 + 3a + 1 = 9*16 + 3*4 + 1 = 157
(3a+1)²-3a
Скобку (3a+1)² можно раскрыть формулой (a+b)² = a² + 2ab + b²
(3a+1)² = 9a²+6a+1
9a²+6a+1-3a
9a²+3a+1, сопоставим a=4
9×4²+3×4+1 = 9×16+3×4+1 = 157
ответ: 157
193
Объяснение:
(3a+1)^2 - 3a = 9a^2 + 6a +1 - 3a = 9a^2 + 3a + 1
Якщо а = 4, то
9a^2 + 3a + 1 = 9*16 + 3*4 + 1 = 157